Race, Ethnicity, and the Relevance of Obesity for Social Integration - Cunningham, Solveig Argeseanu (2012)
OBJECTIVE: To examine race and ethnic differences in the importance of obesity for social integration using the National Longitudinal Study of Adolescent Health (Add Health). DESIGN: A cross-sectional study utilizing survey-adjusted statistics and multivariate logistic and linear regression models. Models were stratified by sex and included interaction terms capturing race, ethnicity and obesity. SETTING: United States of America. PARTICIPANTS: A nationally representative sample of 15,355 respondents grades 7 through 12 who participated in both the In-School and In-Home Wave I surveys of Add Health. MAIN OUTCOME MEASURES: Four self-reported and schoolmate-reported indicators of social integration. RESULTS: The consequences of obesity for social integration are greatest for White adolescents, who were selected by almost 2 fewer schoolmates as friends and had half the odds of having their friendships reciprocated compared with non-obese White adolescents. The social disadvantage of obesity was lower for non-White adolescents; though they are selected by significantly fewer schoolmates as friends and were less likely to have their friendships reciprocated, they did not face additional discrimination from being both obese and minority. CONCLUSIONS: There are significant differences between obese and non-obese adolescents by race and ethnicity in friendships. As friendships are among the most valued assets in adolescence, understanding the impact of obesity on access to friendships for diverse adolescents is a necessary component to understanding the complex motivations that guide health-related behavior at these formative ages.